2021
DOI: 10.1016/s1473-3099(20)30995-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of suvratoxumab for prevention of Staphylococcus aureus ventilator-associated pneumonia (SAATELLITE): a multicentre, randomised, double-blind, placebo-controlled, parallel-group, phase 2 pilot trial

Abstract: Background: Staphylococcus aureus remains a common cause of ventilatorassociated pneumonia, with little change in infection rates over the past 15 years. This phase 2 study evaluated suvratoxumab, an anti-alpha-toxin monoclonal antibody, in reducing incidence of S. aureus pneumonia in intensive care unit (ICU) subjects on mechanical ventilation (MV). Methods:We did a multicenter, single-dose, randomized, placebo-controlled, doubleblind, phase 2 pilot trial in 9 countries. Eligible subjects were patients in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…The antibody was not effective in preventing S . aureus –induced pneumonia in intensive care patients, 37 but its effects on thrombus stabilization has not been assessed before now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibody was not effective in preventing S . aureus –induced pneumonia in intensive care patients, 37 but its effects on thrombus stabilization has not been assessed before now.…”
Section: Discussionmentioning
confidence: 99%
“…Although the monoclonal antibody tested in this study had nearly no effect on Hla-induced lysis of platelets, a humanized Hla neutralizing antibody (MEDI4893*) 36 inhibited organ damage in S. aureus sepsis in animal models 11 and is well tolerated in humans. 35 The antibody was not effective in preventing S. aureus-induced pneumonia in intensive care patients, 37 but its effects on thrombus stabilization has not been assessed before now.…”
Section: F I G U R Ementioning
confidence: 99%
“…Subglottic secretion drainage may not shorten the duration of mechanical ventilation or ICU length-of-stay as is once thought [ 45 49 ]. Furthermore, two recent RCTs showed no significant difference in VAP development among ventilated ICU patients receiving probiotic or monoclonal antibody administration than placebo [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surewaard et al recently revealed that α-hemolysin causes rapid platelet aggregation and liver injury, resulting in multi-organ failure during S. aureus sepsis, but these consequences could be avoided in mice treated with MEDI4893 [103]. MEDI4893 has passed Phase 2 clinical studies for the prevention of S. aureus pneumonia in high-risk critical care unit patients in 2020, and more recently, MEDI4893 showed efficacy and safety in preventing S. aureus ventilator-associated pneumonia [104,105]. In addition, AR-301 and ASN100 are two other neutralizing antibodies that have entered clinical trials.…”
Section: Antibodiesmentioning
confidence: 99%